Cognitive performance of 4-6-year-old children: a longitudinal study - Nur Handayani Utami; Rini Sekartini; Risatianti Kolopaking; Besral Besral; Helda Khusun (Indonesian Pediatric Society, 2023)
Background Many children in low and middle-income countries (LMIC) have reduced cognitive abilities, but few studies have explored the influencing factors. Objective To determine the determinants of children's low cognitive development at 4 to 6-year-old. Methods This is a retrospective cohort study in year 2021. The data was obtained from Bogor Longitudinal Study of Child Growth and Development (BLSCGD) that started from year 2012. For this analysis, we considered 165 of children aged 4-6 years. The dependent variable in this analysis was cognitive development as measured by the Indonesian Wechsler Preschool and Primary Scale of Intelligence (WPPSI) with the indicators of full-scale IQ (FSIQ), verbal IQ (VIQ) and performance IQ (PIQ). The independent variables were determinants of children’s cognitive development at 4-6 years, consisted of socio-demographic factors, determinants from early life (0-23 months), as well as determinants from current conditions. Multivariate analysis done with the logistic regression test. Results Bivariate analysis revealed that paternal education level was significantly associated with FSIQ and inadequate calorie intake in infancy and poor child stimulation were significantly associated with VIQ. In the final model of multivariate analysis, low paternal education level retained a significant association with FSIQ. Psychosocial stimulation was significantly associated with VIQ and inadequate calorie intake during infancy was significantly associated with PIQ. Conclusion Low paternal education level and inadequate psychosocial stimulation are risk factors for reduced child cognitive development in 4-6-year-olds. Inadequate calorie intake in infancy even though not statistically significant it has high OR values for low VIQ and PIQ, thus the results showed the importance of calory intake in infancy.